“PRAGMALINGUISTICS- AN INTEGRAL COMPONENT OF FUNCTIONAL APPROACH” - Hasanova Umida Odiljon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In this article, discourse of pragmatics and the examples in terms of the theory on speech acts were discussed. It also provides with aims and objectives of pragmalinguistics as a science and being a part of grammar, it also considered to be a big part in syntax